Reformulasi Tujuan Pendidikan Islam - M. Edi Suharsongko (Jurnal Alasma : Media Informasi dan Komunikasi Ilmiah, 2021)
Education is the key to progress. The better the quality of education of a nation or community, then it will be better the quality of life of the nation / community. Of the many problems that are a challenge the Islamic world today, is a matter of education. The future of the Islamic world depends on how the Islamic world to answer and soive these challenges. Given that education is important for every human need, community, or nation, then education must always be cuitivated systematically and visionary. Therefore, Islamic education should be designed to follow the rhythm of these changes.